(untitled) (Revista Archai, 2019)
The paper aims to examine some references to the theme of silence within Socratic dialogues. More particularly, the analysis focuses on the importance recognized to the virtue of ÏƒÎ¹Ï‰Ï€á¾¶Î½ in two specific fields: 1) the education of youth and 2) the dialogical exchange. The first aspect is investigated mainly through the exam of Aeschines’ Miltiades, which depicts positively the ability in young people to remain silent (Stob. 2.31, 23; Plu. De recta rat. aud. 4 p. 39b-c) and presents close parallels, in this regard, with some non-Socratic works (especially X. Lac. 3.5 and Isoc. Bus. 28-29). The second aspect, not unrelated to the former, is dealt with by taking into account a reference to the role of silence in Plato’s Protagoras (329b), which sheds light on its anti-Sophistic overtone.